Teleconference system with a shared working space and face mouse interaction - Kim, JH; Ahn, SC; Kim, HG (SPRINGER-VERLAG BERLIN, 2004)
This paper presents a new computer-based teleconference system. In order to build the system, we modified VNC(Virtual Network Computing) program and implemented Face mouse system. Face mouse is a mouse pointer that is followed by face video. It has multiple functions of video communication channel, mouse identification, and a connection between face window and a shared working space. By moving Face mice across a shared working space, the proposed system can provide effective teleconference environment. The proposed system has advantages of providing a larger shared working space and more intuitive interaction than current teleconference systems.